Restorative Justice Concept in Islam & Its Implementation in National Criminal Law from Islamic Legal Philosophy - Fauzi, Rizky; Marpaung, Watni; Prasetya, Nurul Huda (JURNAL AKTA, 2025)
The reform of Indonesia's national criminal law marks a paradigm shift from a retributive punishment system to a Restorative Justice approach that places greater emphasis on victim recovery, social reconciliation, and perpetrator rehabilitation. This principle has been accommodated in various regulations, such as Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, Prosecutor's Regulation No. 15 of 2020, and Article 54 of the new Criminal Code which allows for the consideration of restorative justice in judges' decisions. In Islamic criminal law, the concept of qisas-diyat and the dispute resolution mechanism based on islah (peace) show alignment with restorative justice. Caliph Umar bin Khattab is an example of the application of this approach in a socio-economic context, by postponing punishment for thieves due to starvation. This study uses a normative legal approach with a descriptive-analytical method and a review of maqasid sharia to examine the integration of restorative justice principles in national criminal law. The results of the study indicate that although restorative justice has a place in regulations, its implementation is still limited and faces normative and institutional challenges. Therefore, legislative reform is needed which includes the ratification of special laws, the integration of restorative justice principles in the Criminal Procedure Code Bill, and the expansion of the scope of cases that can be resolved through this mechanism. With a more systematic implementation, restorative justice can become an integral part of the criminal justice system in Indonesia, in line with the principles of Islamic law which emphasize the balance between justice, welfare, and social protection.